Acute poisoning in old and very old patients: a longitudinal retrospective study of 5883 patients in a toxicological intensive care unit - Sieber, Cornel; et al. (Zeitschrift für Gerontologie und Geriatrie, 2005)
Although morbidity and mortality of acute poisoning are increased in elderly compared to younger patients, little has been published on this topics in the last years (Medline search). To investigate the influence of age on the clinical course of acute poisoning with different toxic agents, a longitudinal retrospective study at the Toxicological Intensive Care Unit (ICU) of the 2nd Department of Internal Medicine (Klinikum Niirnberg, Germany) was performed.A total of 5883 patients treated at our toxicological ICU were enrolled into the study, including all patients of the years 1982, 1992, and 1997. These three years were selected to investigate possible time-dependent changes of intoxication characteristics and quality of therapy at our ICU over a time span of 15 years.For each patient the following data were obtained from a standardized toxicological record: age, gender, toxic agents responsible for acute poisoning, and length of stay at the toxicological ICU. For a subgroup of 3740 patients, the cause of acute poisoning and the clinical outcome was also recorded.As compared with younger patients, mean length of stay at the ICU, indicating a more serious course of acute poisoning, was prolonged in elderly and, i.e., in very old patients (p < 0.001). However, this prolongation of time at the ICU was only observed in elderly patients poisoned with drugs or with mixed poisoning including drugs, while mean length of stay was not prolonged in elderly patients poisoned with alcohol, with illegal drugs, chemicals, animal/plant poison, or other toxic agents.Patients with the highest risk of dying in the ICU after acute poisoning were elderly patients attempting suicide with drugs. Mortality in 3740 patients with acute poisoning was 0.24%, while it was 2.17% in the 184 patients being 65 years old or older. Thus, mortality was 9-fold higher in the elderly.Mean length of stay at the ICU decreased significantly from 1982 to 1992 and to 1997 (p < 0.001) indicating an improvement of the therapeutical ICU management of acute poisoning and/or less dangerous toxic agents (i.e. less barbiturates). The age-dependent increase of the length of stay at the ICU until very old age (> 80 years) was most pronounced in 1982 and also declined markedly until 1997.Age, suicide attempt, and ingestion of (multiple) drugs seem to be risk factors for a higher mortality and a prolonged stay in the ICU after acute poisoning. Although in general the clinical course after poisoning has more complications and an impaired prognosis in old age, each category of toxic agents (drugs, alcohol, chemicals, etc.) has its own special "risk profile" for elderly patients. However, due to advances in modern ICU medicine the general prognosis of acute poisoning is good in old and even in oldest old patients.
Keywords: age; acute poisoning; clinical course; intensive care unit; mortality; drugs